Forecasting from Structural Econometric Models. - Hendry, D; Mizon, G (Department of Economics (University of Oxford), 2012)
Understanding the workings of whole economies is essential for sound policy advice - but not necessarily for accurate forecasts. Structural models play a major role at most central banks and many other governmental agencies, yet almost none forecast the financial crisis and ensuing recession. We focus on the problem of forecast failure that has become prominent during and after that crisis, and illustrate its sources and many surprising implications using a simple model. An application to ‘forecasting’ UK GDP over 2008(1)-2011(2) is consistent with our interpretation.